Circadian Regulation of Gene Expression and Metabolism in the Liver - Guan, Dongyin; Lazar, Mitchell A. (Seminars in Liver Disease, 2022)
Circadian rhythms are approximately 24-hour cycles of variation in physiological processes, gene expression, and behavior. They result from the interplay of internal biological clocks with daily environmental rhythms, including light/dark and feeding/fasting. Note that 24-hour rhythms of liver metabolic processes have been known for almost 100 years. Modern studies reveal that, like metabolism, hepatic gene expression is highly rhythmic. Genetic or environmental changes can disrupt the circadian rhythms of the liver, leading to metabolic disorders and hepatocellular carcinoma. In this review, we summarize the current understanding of mechanisms regulating rhythmic gene expression in the liver, highlighting the roles of transcription factors that comprise the core clock molecular as well as noncanonical regulators. We emphasize the plasticity of circadian rhythms in the liver as it responds to multiple inputs from the external and internal environments as well as the potential of circadian medicine to impact liver-related diseases.
Keywords: circadian rhythm; metabolism; gene expression